Giggle Gift & Delivery - Abdul Wahab, Amna Humaira; Abu Bakar, Alis Syamila; Khairul Anuar, Amirah; C.W. Asmawi, C.W. Nur Aisyah Farhah; Che Wan Azmi, Che Wan Nor Syuhirah Aisyah (2025)
Giggle Gift & Delivery, established in 2023, is a Kuala Lumpur–based service company specializing in professional gift wrapping and direct delivery to help customers surprise their loved ones with thoughtfully prepared gifts. The company offers two main services: wrapping customer-provided gifts or purchasing, customizing, and wrapping gifts on their behalf. With departments spanning administration, finance, operations, marketing, sales, technical development, and delivery, the company ensures smooth operations and high-quality service. Located strategically in Boulevard Business Park, it serves a wide target market including youths, couples, and anyone seeking affordable yet beautifully wrapped gifts requiring bookings at least three days in advance to ensure timely preparation and delivery.